UML for the IT business analyst, a practical guide to requirements gathering using the unified modeling language - Podeswa, Howard (Australia, 2010)
The book is about the IT Business Analyst and the requirements on how they gather using the unified modeling language.
Keywords: Object-Oriented Methods (Computer science); UML (Computer Science)